Complex pBAE Nanoparticle Cell Trafficking: Tracking Both Position and Composition Using Super Resolution Microscopy. (18th March 2022) - Riera, Roger; Tauler, Jana; Feiner‐Gracia, Natàlia; Borrós, Salvador; Fornaguera, Cristina; Albertazzi, Lorenzo
Abstract: Nanomedicine emerged some decades ago with the hope to be the solution for most unmet medical needs. However, tracking materials at nanoscale is challenging to their reduced size, below the resolution limit of most conventional techniques. In this context, we propose the use of direct stochastic optical reconstruction microscopy (dSTORM) to study time stability and cell trafficking after transfection of oligopeptide end‐modified poly(β‐aminoester) (OM‐pBAE) nanoparticles. We selected different combinations of cationic end oligopeptides (arginine – R; histidine – H; and lysine – K) among polymer libraries, since the oligopeptide combination demonstrated to be useful for different applications, such as vaccination and gene silencing. We demonstrate that their time evolution as well as their cell uptake and trafficking are dependent on the oligopeptide. This study opens the pave to broad mechanistic studies at nanoscale that could enable a rational selection of specific pBAE nanoparticles composition after determining their stability and cell trafficking. Abstract : Polyplexes are cationic polymer nanoparticles carrying oligonucleotides as therapeutic agents for gene delivery. Single‐molecule localization microscopy techniques, such as STORM, are powerful tools to visualize the structure of polyplexes beyond the theoretical resolution limit and quantitatively measure their composition. With STORM we are able to measure the packing of different pBAE polyplexes and track the decomplexation and cargo release inside COS‐7 cells.